Effectiveness of a bounty program for reducing wild pig densities - Stephen S. Ditchkoff; Robert W. Holtfreter; Brian L. Williams (Wildlife Society Bulletin)
ABSTRACT Bounty programs have been historically implemented as a means of controlling invasive or pest species. Although bounty programs are generally considered to be ineffective, they are still proposed as management tools in situations where other management strategies have been unsuccessful. The wild pig (Sus scrofa) is an invasive large mammal in North America and most management strategies have proven to be ineffective at reducing or eliminating its populations, resulting in population expansion in recent decades. Fort Benning Army Infantry Training Center, Georgia, USA, had been inhabited by wild pigs since the mid‐1900s. In response to increasing negative impacts on flora, fauna, and military training activities and equipment, Fort Benning began offering a bounty on pigs in June 2007 to reduce the population and eventually eradicate wild pigs from the installation. To gauge the effectiveness of the program, we evaluated the population response of wild pigs within 2 study areas on the installation from June 2007 to February 2008. During the study, 1,138 pigs were harvested throughout the installation at a total cost (bounties paid and administration) of US$57,296. Surveys indicated that pig density and occupancy rates increased 23–130% and 12–19%, respectively, during the course of the bounty program. Additionally, sounder size and number of juveniles per adult female increased 144–233% and 191–219%, respectively. These data suggest that the wild pig population was increasing during the period when the bounty program was in effect. We hypothesize that this was due to increased food availability and reproduction associated with baiting wild pigs during the program, and because efforts of program participants were focused on eliminating the segment of the pig population that would maximize return on effort and “trophy” quality of animals rather than on the segment of the population that would most greatly influence population growth. © 2017 The Wildlife Society.